Enhancing Type 2 Diabetes Management through Patient-Centric Pharmacist Counselling: A Comprehensive Study - Fernando, Thanuji; Munasinghe, Chathula; Liyanaarachchi, Hasitha; Nelumdeniya, Rumesh; Fernandopulle, Rohini (Indian Journal of Pharmacy Practice)
Introduction: Patient counselling has been shown to significantly enhance lifestyle modifications and medication adherence in the management of non-communicable diseases. Research Design and Methods: A single-centre, prospective, randomized, controlled, interventional study was conducted at a leading tertiary care hospital in Sri Lanka to investigate the impact of pharmacist-led patient counselling on Knowledge, Attitude and Practice (KAP) based lifestyle changes and treatment in Type 2 Diabetic Mellitus (T2DM). Baseline KAP scores were initially assessed via a comprehensive questionnaire administered to all participants. Subsequently, only the test group received targeted counselling from a pharmacist, complemented by a detailed educational leaflet. Results: After 2 months, a follow-up assessment revealed a significant increase in the test group’s mean KAP score from 39.11±5.82 to 49.02±3.39 (p=0.00; p<0.05), indicating the effectiveness of the intervention. Furthermore, there was a marked improvement in the test group’s average Fasting Blood Sugar (FBS) levels, which decreased from 147.58±43.30 mg/dL to 134.13±40.02 mg/dL. A positive correlation was observed between baseline knowledge and educational level (p=0.012), underscoring the role of education in disease management. However, no significant changes were noted in Body Mass Index (BMI) in either group (p>0.05). Conclusion: This study demonstrates that enhancing KAP through patient counselling can positively influence the overall management of T2DM.
Keywords: Patient Counselling; Knowledge; Attitude; Practice; Type 2 DM